The Effectiveness of Movies as a Teaching Learning Media to Improve Students’ Learning Achievement at Eleventh Grade of SMK Rise Kedawung Cirebon - Tia Karlina (Riviera Publishing, 2022)
Learning achievement is the acquisition of knowledge or skills that usually indicated by test scores in the form of numerical value. By using movies to teach can definitely be a challenge, but when carried out in a proper manner, it boasts of numerous benefits. Unlike text, movies enable students to learn visually. This research aims to determine the interactive effects of movies as a teaching learning media to improve students’ learning achievement. The researcher used experimental research with quantitative approach. The sample of this research was 35 respondents, randomly selected from eleventh grade of SMK RISE Kedawung Cirebon. Pre-experimental design was used in this research and pretest and posttest design of pre-experimental design became ultimate choice in this research. Based on data analysis the researcher concludes that there was increase of gaining score of the students after movies treatment. On levels of significance 0.05, the researcher found that t-observed of data is 29.70, and the degree of freedom is 34 which is converted to the t-value of 2.03. Based on the data from the test, it is clear that t-observed is higher than t-value. In fact, t-observed > t-value (29.70 > 2.03), it means that the treatment of movies as a teaching learning media is effective to improve students’ learning achievement.